A Comparative Study of Mystical-Visual Expression of Nizami Stories in Two Paintings of Haft Peykar and the Death of Shirin by Emphasizing the Relationship between Visual Structure and Story Context - Zeinab Rajabi; Khashayar Ghazizadeh (Journal of Visual Art and Design, 2018)
Nizami is one of the most famous poets of the sixth century. His mystical and romantic stories are full of wisdom. His two stories called 'Haft Peykar' and 'Khosrow and Shirin', which are discussed in this article, have interested artists throughout the history of Iranian art. The painter of the 'Haft Peykar' painting shows the whole story from beginning to end in one single image. The painter of the 'Death of Shirin' painting, emphasizes the paradoxes of life, the confrontation of life and death, heaven and earth, and loyalty and betrayal in the composition, colors and symbolic elements. This study used an analytical-descriptive method. The purpose of this research was to determine how the painters used these two mystical literary texts to express their own ideas. What can be seen from the two paintings is that the artists used the stories of Nizami to create their works with an artistic and mystical visual language, using symbolism in the composition and the colors. It should be noted that the painters also added meanings to their paintings and thus presented new content for the viewer.